1985
DOI: 10.1152/jappl.1985.59.6.1911
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual cycle on thermoregulatory, metabolic, and heart rate responses to exercise at night

Abstract: Ten women [mean maximal O2 uptake (VO2max), 2.81 l X min-1] exercised for 15 min on a cycle ergometer in the middle of the luteal phase (L) and in the early follicular phase (F) of the menstrual cycle at the same constant work rates (mean 122 W) and an ambient temperature of 18 degrees C. Serum progesterone averaged 44.7 nmol X l-1 in L and 0.7 nmol X l-1 in F. After a 4-h resting period, exercise was performed between 3 and 4 A.M., when the L-F core temperature difference is maximal. Preexercise esophageal (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
2
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 0 publications
12
77
2
2
Order By: Relevance
“…The finding of the present study that the performance, rectal temperature, heart rate and perceived exertion of unacclimatised eumennorheic women during intermittent running in the heat (31 ± 0.2 o C; 23.1 ± 0.9% RH) were unaffected by menstrual cycle phase is largely consistent with previous research examining other modes of exercise (Wells and Horvath 1974;Horvath and Drinkwater 1982 temperature between the luteal and follicular phase are observed) in moderate environmental conditions after a 4 h rest period in the heat, rectal temperature, heart rate, sweating thresholds and oxygen uptake were all lower during the follicular in comparison with the luteal phase (Hessemer and Brück 1985). Thus, in the present study, while the similar running performance in the follicular and luteal phases of the cycle is entirely consistent with previous cycling and walking studies, the lack of any effect on deep body temperature or cardiovascular responses may be explained by the unacclimatised status of the subjects and the intense nature of the exercise.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of the present study that the performance, rectal temperature, heart rate and perceived exertion of unacclimatised eumennorheic women during intermittent running in the heat (31 ± 0.2 o C; 23.1 ± 0.9% RH) were unaffected by menstrual cycle phase is largely consistent with previous research examining other modes of exercise (Wells and Horvath 1974;Horvath and Drinkwater 1982 temperature between the luteal and follicular phase are observed) in moderate environmental conditions after a 4 h rest period in the heat, rectal temperature, heart rate, sweating thresholds and oxygen uptake were all lower during the follicular in comparison with the luteal phase (Hessemer and Brück 1985). Thus, in the present study, while the similar running performance in the follicular and luteal phases of the cycle is entirely consistent with previous cycling and walking studies, the lack of any effect on deep body temperature or cardiovascular responses may be explained by the unacclimatised status of the subjects and the intense nature of the exercise.…”
Section: Discussionsupporting
confidence: 89%
“…VO2max appears to be largely unaffected by the phase of the menstrual cycle [80,81]. However, some studies have shown increased minute ventilation [39,[82][83][84], heart rate [84][85][86] and rating of perceived exertion [84,85] during the luteal phase, which could be attributed to an increased core temperature (0.3 -0.5 °C) during this phase [84]. Lactate threshold findings are equivocal with some reports of stable values throughout the cycle [87,88], whilst others describe lower blood lactate concentrations in the luteal phase during moderate-intensity activity [89].…”
Section: 1)mentioning
confidence: 99%
“…Some studies measuring REE in healthy female premenopausal adults during the menstrual cycle have described a slight increase (5-9%) in REE in the luteal (Hessemer and Bruck, 1985;Webb, 1986) compared with the follicular phase, although others have shown no difference in REE between the two phases (Howe et al, 1993;Piers et al, 1995). However, the weight of evidence points to cyclical changes in REE during the menstrual cycle (The National Academy of Sciences, 2002).…”
Section: Discussionmentioning
confidence: 99%